Chromosomal similarities and differences among four Neotropical Elateridae (Conoderini and Pyrophorini) and other related species, with comments on the NOR patterns in Coleoptera - Schneider, M. C. [UNESP]; Rosa, S. P.; Almeida, M. C.; Costa, C.; Cella, D. M. [UNESP] (Hindawi, 2007)
This work deals with the comparative cytogenetic analysis of four Neotropical Elateridae species and reviews the nucleolar organizer region (NOR) patterns on Coleoptera chromosomes, for the first time. The cytogenetic characterization of Conoderus malleatus (Conoderini), Pyrearinus candelarius, Pyrophorus divergens and Pyrophorus punctatissimus (Pyrophorini) was accomplished through the study of mitotic and meiotic cells submitted to standard (Giemsa) and differential staining [silver impregnation and GC-specific chromomycin A 3 (CMA 3) plus AT-specific 4′-6-diamidino-2-phenylindole (DAPI) fluorochromes]. The analysis of spermatogonial cells revealed the diploid numbers: 2n = 17 in C. malleatus and 2n = 15 in P. candelarius, P. divergens and P. punctatissimus. In these species, the X0 type sex-determination system and the acrocentric morphology of almost all chromosomes were observed. The study of meiotic cells of the four species revealed the occurrence of total synapsis between the autosomes, the presence of one terminal or interstitial chiasma in the majority of the bivalents, and the reductional behaviour and regular segregation of all chromosomes. Although the three Pyrophorini species demonstrated many similar karyotypical characteristics, there was one discrepancy, which was noted in the diplotene cells and concerns the number of bivalents with two chiasmata; P. candelarius only presented one bivalent, P. divergens showed two bivalents and P. punctatissimus exhibited up to four bivalents with two chiasmata. Testicular cells impregnated with silver nitrate demonstrated two terminal NORs located on the fourth autosomal pair of the Conoderini species and on the second autosomal pair of the three Pyrophorini representatives. Use of CMA 3/distamycin A (DA)/DAPI staining on the P. candelarius and P. punctatissimus chromosomes revealed that the CMA 3 labelled regions were coincident with the NORs. The main strategies of karyotypical differentiation that have occurred among the four Elateridae species and other related species, and the general trends of the NOR shifts during Coleoptera chromosomal evolution are discussed in this work. © 2007 The Authors.
Keywords: Bivalent; Chiasma; Fluorochrome; Karyotype; Meiosis; Sex-determination system; beetle; chromosome; cytogenetics; morphology; relatedness; sex determination; Coleoptera; Conoderus; Elateridae; Pyrearinus; Pyrophorus; Synapsis